PENGEMBANGAN LEARNING MANAGEMENT SYSTEM (LMS) DENGAN METODE GAMIFIKASI UNTUK PENDIDIKAN EKONOMI NON-FORMAL - Indra Febrianto (Dharma Pendidikan, 2025)
Background: Along with the evolving demands of the business world today, there are increasing challenges in non-formal economic education to address the need for fostering young entrepreneurs in Indonesia. To date, existing non-formal economic education processes have yet to adequately accommodate learners' needs for hands-on learning experiences (learning by doing). Objective: This study aims to develop a Learning Management System (LMS) by applying gamification methods to support non-formal economic education. The use of gamification is expected to enhance learners' motivation and engagement in the learning process, enabling them to achieve the desired competencies. Method: The development method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The analysis phase identifies user needs and learning materials. In the design phase, gamification elements such as points, badges, leaderboards, and quests are structured to improve user interaction. The development phase produces an LMS prototype with gamification features using the Moodle framework. Implementation was conducted among micro-entrepreneurs, with excellent acceptance rates. Evaluation through questionnaires and learning tests demonstrated increased motivation and comprehension of economic concepts through gamified simulations within the LMS. Results: The findings prove that a gamified LMS is effective in supporting non-formal economic education. Conclusion: The study concludes that gamification in LMS can serve as an innovative solution to enhance engagement and learning outcomes in non-formal education, particularly in economics. Future research should explore adaptive learning features to personalize the learning experience.